2017
DOI: 10.1021/jacs.7b05313
|View full text |Cite
|
Sign up to set email alerts
|

Protospacer Adjacent Motif-Induced Allostery Activates CRISPR-Cas9

Abstract: CRISPR-Cas9 is a genome editing technology with major impact in life sciences. In this system, the endonuclease Cas9 generates double strand breaks in DNA upon RNA-guided recognition of a complementary DNA sequence, which strictly requires the presence of a protospacer adjacent motif (PAM) next to the target site. Although PAM recognition is essential for cleavage, it is unknown whether and how PAM binding activates Cas9 for DNA cleavage at spatially distant sites. Here, we find evidence of a PAM-induced allos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
186
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 122 publications
(207 citation statements)
references
References 20 publications
18
186
0
3
Order By: Relevance
“…The SPL: A Protein-Directed Ribozyme. To characterize the SPL functional dynamics and the leading role of Spp42, the largest and the most important protein of the SPL, we have computed the cross-correlation scores (CSs) for each pair of SPL components (i.e., RNAs and proteins, explicitly considering the Spp42 domains and N-terminal motifs), which enable to qualitatively measure their interdependent dynamical coupling (27)(28)(29). The CSs histogram for ILS-1 model (Fig.…”
Section: Cwf15mentioning
confidence: 99%
“…The SPL: A Protein-Directed Ribozyme. To characterize the SPL functional dynamics and the leading role of Spp42, the largest and the most important protein of the SPL, we have computed the cross-correlation scores (CSs) for each pair of SPL components (i.e., RNAs and proteins, explicitly considering the Spp42 domains and N-terminal motifs), which enable to qualitatively measure their interdependent dynamical coupling (27)(28)(29). The CSs histogram for ILS-1 model (Fig.…”
Section: Cwf15mentioning
confidence: 99%
“…for understanding the molecular basis of the CRISPR-Cas9 function. (13)(14)(15)(16)(17) Among other studies, our group has successfully applied MD simulations to disclose a mechanism for the conformational activation of Cas9, clarifying the activation process by which the HNH domain is repositioned for cleavage in good agreement with structural and smFRET experiments. (18) Remarkably, MD simulations as well as experimental studies have indicated that the conformational changes underlying the CRISPR-Cas9 function occur over and beyond micro-to-millisecond time scales.…”
Section: Introductionmentioning
confidence: 81%
“…(18,34) As well, L1/L2 exert an allosteric control on the activity of HNH and RuvC, enabling the information transfer for concerted cleavages of the two DNA strands. (15,35) In order to understand the role of these two loops in the interaction with the hybrid, we specifically measured the interactions established by L1/L2 and the DNA:RNA hybrid. As a result, the interactions of L1 do not show relevant differences among the investigated systems ( Fig.…”
Section: Effect Of Off-target Binding On the Catalytic Domainsmentioning
confidence: 99%
“…Over the past decade, MD simulations have become increasingly important in solving the atomiclevel mechanisms of protein allostery, often revealing missing features that purely experimental techniques could not provide (16)(17)(18)(19). However, a lack of sufficient sampling of events that take place on very large timescales constitutes a significant limitation when employing standard MD simulations to explore allosteric mechanisms.…”
Section: Introductionmentioning
confidence: 99%